Motivation and Independence in Learning in Nursing New Students - Komariah, Ade; Fiana, Marista; Ningsih, Rastia (Java Nursing Journal, 2024)
Background: In the first year of study, students face academic, social adjustment, campus environmental, and learning system changes that require them to study independently, which can lead to conflicts between students who are still adjusting to their new role and those who must complete nursing tasks. Purpose: This research aims to determine learning independence which is influenced by learning motivation in new students of the Bachelor of Nursing study program. Methods: A total of 120 new students from the class of 2023 were involved in this research. The instruments used are the learning independence scale and the learning motivation scale. The data analysis used is assumption testing, hypothesis testing and difference testing. The results show: 1) based on the assumption test that the research data is proven to be normal and linear. Findings: based on hypothesis testing that there is a positive relationship between learning motivation and learning independence (r = 0.770; p < 0.01), and there is an influence of learning motivation on learning independence of (R² = 0.592; p < 0.01); 3) based on different tests that there are differences in learning independence based on student demographic factors [F= 1.321, p< 0.05]. Conclusion: This study shows that learning motivation helps new students learn independently. Students with high intrinsic and extrinsic motivation gain from learning freedom, and vice versa